Simulation study of processes in multi-channel led current regulator - L. S. Kazarinov; E. V. Vstavskaya; G. A. Saeed (Известия высших учебных заведений: Проблемы энергетики)
In this paper we study the effect of variation of parameters on stabling LED current regulator. Diagram of three-channel LED current regulator is developed. Modeling of three-channel regulator and their results in VisSim are shown. Control channel’s system using microcontroller with square and sawtooth impulses is investigated.